Construction of a plastomer for the analysis of polypropylene fluidity under different temperatures and use of additives - Frizzo, Juliano (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
A low-cost plastomer was built and analyzed the main factors that can improve its fluidity, such as the use of different specifications and additives. Thermoplastics are materials currently used everywhere, from simple applications such as making toys to aerospace applications. Among the usual thermoplastics in our daily lives we have polypropylene, widely used as raw material for the manufacture of various plastic materials. One of the factors that most interferes with the quality of PP in industrial use is its fluidityindex, measured by the use of plastomer, an extremely expensive equipment. From the analysis of various temperatures and percentages of additives it was possible to identify factors that improve its fluidity, improving industrial applicability. It is concluded that there is a direct relationship between the increase in the melt index (fluidity index) of the melt and the increase in temperature and additives by up to 1%, emphasizing that with 2% worse results can be obtained from the IF. This increase in the bottom IF can be explained by the theory of free volume, where the higher the temperature, the greater the free volume between the molecules and the lower their viscosity, that is, the easier their flow will be.